β-Myosin Heavy Chain Variant Val606Met Causes Very Mild Hypertrophic Cardiomyopathy in Mice, but Exacerbates HCM Phenotypes in Mice Carrying Other HCM Mutations - Blankenburg, Robert; Hackert, Katarzyna; Wurster, Sebastian; Deenen, René; Seidman, J.G.; Seidman, Christine E.; Lohse, Martin J.; Schmitt, Joachim P. (Circulation research, 2014)
RATIONALE:Approximately 40% of hypertrophic cardiomyopathy (HCM) is caused by heterozygous missense mutations in β-cardiac myosin heavy chain (β-MHC). Associating disease phenotype with mutation is confounded by extensive background genetic and lifestyle/environmental differences between subjects even from the same family. OBJECTIVE:To characterize disease caused by β-cardiac myosin heavy chain Val606Met substitution (VM) that has been identified in several HCM families with wide variation of clinical outcomes, in mice. METHODS AND RESULTS:Unlike 2 mouse lines bearing the malignant myosin mutations Arg453Cys (RC/+) or Arg719Trp (RW/+), VM/+ mice with an identical inbred genetic background lacked hallmarks of HCM such as left ventricular hypertrophy, disarray of myofibers, and interstitial fibrosis. Even homozygous VM/VM mice were indistinguishable from wild-type animals, whereas RC/RC- and RW/RW-mutant mice died within 9 days after birth. However, hypertrophic effects of the VM mutation were observed both in mice treated with cyclosporine, a known stimulator of the HCM response, and compound VM/RC heterozygous mice, which developed a severe HCM phenotype. In contrast to all heterozygous mutants, both systolic and diastolic function of VM/RC hearts was severely impaired already before the onset of cardiac remodeling. CONCLUSIONS:The VM mutation per se causes mild HCM-related phenotypes; however, in combination with other HCM activators it exacerbates the HCM phenotype. Double-mutant mice are suitable for assessing the severity of benign mutations.